Unconventional Spin State Driven Spontaneous Magnetization in a Praseodymium Iron Antimonide. Issue 8 (28th December 2022) - Pabst, Falk; Palazzese, Sabrina; Seewald, Felix; Yamamoto, Shingo; Gorbunov, Denis; Chattopadhyay, Sumanta; Herrmannsdörfer, Thomas; Ritter, Clemens; Finzel, Kati; Doert, Thomas; Klauss, Hans‐Henning; Wosnitza, Jochen; et al.
Abstract: Consolidating a microscopic understanding of magnetic properties is crucial for a rational design of magnetic materials with tailored characteristics. The interplay of 3d and 4f magnetism in rare‐earth transition metal antimonides is an ideal platform to search for such complex behavior. Here the synthesis, crystal growth, structure, and complex magnetic properties are reported of the new compound Pr3 Fe3 Sb7 as studied by magnetization and electrical transport measurements in static and pulsed magnetic fields up to 56 T, powder neutron diffraction, and Mößbauer spectroscopy. On cooling without external magnetic field, Pr3 Fe3 Sb7 shows spontaneous magnetization, indicating a symmetry breaking without a compensating domain structure. The Fe substructure exhibits noncollinear ferromagnetic order below the Curie temperature T C  ≈ 380 K. Two spin orientations exist, which approximately align along the Fe–Fe bond directions, one parallel to the ab plane and a second one with the moments canting away from the c axis. The Pr substructure orders below 40 K, leading to a spin‐reorientation transition (SRT) of the iron substructure. In low fields, the Fe and Pr magnetic moments order antiparallel to each other, which gives rise to a magnetization antiparallel to the external field. At 1.4 K, the magnetization approaches saturation above 40 T. The compound exhibits metallic resistivity along the c axis, with a small anomaly at the SRT. Abstract : The novel rare‐earth transition metal antimonide Pr3 Fe3 Sb7 shows spontaneous magnetization when cooled without external magnetic field, indicating a symmetry breaking without a compensating domain structure. Below 40 K, the Fe and Pr magnetic moments order antiparallel to each other, which gives rise to a magnetization antiparallel to the external field. The spin structure is studied by magnetic measurements, spectroscopy, and diffraction.